OCORRÊNCIA DA INFECÇÃO POR Bartonella sp. E Ehrlichia sp. EM CÃES (Canis lupus familiaris) E GATOS (Felis catus) DE CAMPO GRANDE, MS - Camila Maria dos Santos (2023)
The casuistry of vector-borne agents has a high occurrence in small animal clinics. The Center West region of Brazil presents a high detection of pathogens transmitted by vectors that have zoonotic character. Knowing this, there is a need of monitoring for the implementation of prevention and control measures. The aim of this work was to evaluate the presence and previous contact of Bartonella sp. and Ehrlichia sp. in dogs and cats seen at the veterinary clinic of Anhanguera Uniderp University in the year 2019. Ninety-three samples from dogs and 45 from cats were used. The samples of whole blood and serum were collected from animals seen in the routine of the Clinic of the Anhanguera Uniderp University. Of the 93 dogs examined, 71(76%) serum samples were reagent to IFI of Ehrlichia canis and in 30 blood samples Ehrlichia sp. DNA was detectable, with a total prevalence of 78% of positive dogs for erliquiosis. Analysis of statistical models showed that young, male dogs with thrombocytopenia and anemia are suggestive of a positive test for Ehrlichia sp. DNA from Bartonella sp. was not detected in any dog sample, but there was a seroprevalence of 12% (11/93). This is the first study to report the exposure of dogs to Bartonella henselae in Campo Grande, MS. Regarding cats, from 45 blood samples, one tested positive for Ehrlichia sp. DNA and from 30 serum samples analyzed by IFI, 3 (10%) were seroreagent. Thirty serum samples from cats were tested for RIFI for Bartonella henselae, with a seroprevalence of 40% (12/30), while Bartonella sp. DNA was detected in 5 (11%) of 45 samples analysed. Due to lack of data no clinical signs or haematological alterations were compared to the results of the positive cats. These results show a high occurrence of erliquiosis in dogs in the studied population and the exposure of domestic animals in the city of Campo Grande - MS to Bartonella sp., still little studied in the state, as well as the identification of cats positive for Bartonella sp. DNA, alert to the risk of transmission of this zoonosis to humans.